ANALYSIS STRUCTURE OF THE NEW BUILDING PKU MUHAMMADIYAH ISLAMIC HOSPITAL TEGAL - Ramadhan, Yusril; Firmanto, Arief (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2019)
ABSTRACTMuhammadiyah Islamic Hospital Tegal, built a 5 floor building to improve the quality of services in the health sector. Health access and more complete services in the district of Tegal are indeed expected by the community so that the community can get better health services.Muhammadiyah Islamic Hospital Tegal used a reinforced concrete structure and designed with reference to SNI 1727 :2013, PPURG 1987, SNI 2847 :2013 and SNI 1726 :2012.The static equivalent and the dynamic response spectrum analysis method is used in analyzing earthquakes load. The earthquake force on the structure is used a configuration of the structure of the Special Moment Resisting Frame System (SMRFS).Analysis structure at this building used a software ETABS v9.6.0to help structure modeling and calculate internal forces acting on the structure.Keyword: SNI 1727:2013, PPURG 1987, SNI 2847:2013, SNI 1726:2013, Response Spectrum, Lateral Equivalent Analysis, SMRF, ETABS v9.6.0